The Effect of Brand Communities on Public Brand Loyalty And Private Brand Loyalty Of Professional Electronic Sports Team - Muhammad Hidayat; Budi Astuti (International Journal of Economics, Business and Innovation Research, 2024)
Each e-sports team usually has a loyal and fanatic fan community. Fans often participate in supporting their favorite teams through various activities such as watching tournaments, fan meetings, and purchasing official merchandise. In the competitive e-sports industry, a team's presence must stand out more than others to be better recognized by consumers. This research aims to understand the potentially different impacts of brand community identification on the relationship between brand identification and various aspects of brand loyalty. This study identifies the influence of the brand community on brand loyalty, both from a public and private perspective, particularly in the context of electronic sports. This research uses a quantitative approach and convenience sampling technique conducted with 122 respondents who are fans of an electronic sports team. The SEM smartPLS analysis results show that brand identification and brand community positively and significantly influence both public and private brand loyalty. This research provides insights into the impact of brand identification and brand community on the public and private brand loyalty that consumers have towards a brand. Thus, it will help marketing managers to more effectively utilize brand communities in generating consumer behavior that supports the brand.